Vested interests and trade policy-making: the influence of business and NGOs in transition and developing economies - Kostecki, Michał Maciej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
It is often claimed that globalization suffers from a deficit of democracy. What is the place of advocacy by various interest groups in the process of trade policy-making and international trade negotiations which shape transition economy and developing country participation in the global trading system? What is and what should be the role of companies and business organizations in these processes? How to encourage government responsiveness to trade-related concerns of the business community? How to promote the interest of the private sector and civil society in international trade negotiations, such as the Doha Round? This study provides an overview of the issue, discusses the results of a behaviourist study conducted in the milieu of business, civil society and government, and offers suggestions on how to improve business-government interactions in trade policy-making of the countries concerned
Argumenta Oeconomica, 2007, No 1-2 (19), s. 97-124
Keywords: economic development; Business advocacy; Lobbying; trade policy; governance; Businessgovernment relations; NGOs